2022
DOI: 10.3389/fgene.2022.889530
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Long Noncoding RNA LINC00673 Genetic Variants on Susceptibility to Diabetic Retinopathy

Abstract: Long noncoding RNAs (lncRNAs) have been proven to play critical roles in diabetic retinopathy (DR). This study investigated whether the single nucleotide polymorphism (SNP) of long intergenic noncoding RNA 00673 (LINC00673) affects the clinical characteristics of diabetic retinopathy (DR). A total of three loci of LINC00673 SNPs (rs6501551, rs9914618, and rs11655237) were genotyped using TaqMan allelic discrimination in 276 and 454 individuals with and without DR, respectively. Our results revealed that LINC00… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…There are some factors that affect the development and progression of DR. A higher glycated hemoglobin (HbA1c) level, a longer duration of diabetes mellitus, hypertension, and dyslipidemia are associated with diabetic retinopathy (Cheung et al, 2010;Lin et al, 2021). Moreover, genetic factors play an essential role in DR, and genetic studies show a racial variation in DR's incidence (Simó-Servat et al, 2013;Cho and Sobrin, 2014;Mankoč Ramuš et al, 2021;Chuang et al, 2022a;Chuang et al, 2022b;Lee et al, 2022). Genome-wide analysis of DNA methylation in patients with type 1 diabetes mellitus found that this is associated with PDR (Agardh et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…There are some factors that affect the development and progression of DR. A higher glycated hemoglobin (HbA1c) level, a longer duration of diabetes mellitus, hypertension, and dyslipidemia are associated with diabetic retinopathy (Cheung et al, 2010;Lin et al, 2021). Moreover, genetic factors play an essential role in DR, and genetic studies show a racial variation in DR's incidence (Simó-Servat et al, 2013;Cho and Sobrin, 2014;Mankoč Ramuš et al, 2021;Chuang et al, 2022a;Chuang et al, 2022b;Lee et al, 2022). Genome-wide analysis of DNA methylation in patients with type 1 diabetes mellitus found that this is associated with PDR (Agardh et al, 2015).…”
Section: Introductionmentioning
confidence: 99%